Membongkar Veto Player dalam Politik Kepartaian Indonesia Menuju Pemilu 2014 - Budi, Arya (Jurnal Ilmu Sosial dan Ilmu Politik, 2013)
The article explains about how party elites, then identified as veto players, in Indonesiaâs 2014 election organize themselve into party organization. The authority institutionalization of the veto player creates a decisional and positional quadrant of each party in terms of party politics of 2014 election. The findings of veto player pattern in such a party politics confirm forms of a centripetal force of politics in party organization. Finally, veto player behavior causes a spectrum of political cybernetics among political parties based on its turbulence, cohesiveness, and switching elites.